Evidence for Resilient Agriculture (ERA). Speed talk presentation - Rosenstock, Todd S.; Lamanna, Christine; Namoi, Nictor; Kamau, Hannah N.; Steward, Peter R.; Nowak, Andreea C. (2019)
Speed talk presentation at the Global Science Conference for Climate-Smart Agriculture, 8-11 October 2019. Bali, Indonesia.